Rectal Reconstruction after Total Mesorectumectomy: Functional Outcomes and Quality of Life - A. O. Rasulov; A. B. Baychorov; A. M. Merzlyakova; A. I. Ovchinnikova; A. V. Semyanikhina (Креативная хирургия и онкология, 2021)
Background. The study aims to compare the functional outcomes and quality of life in patients having variant rectal reconstruction procedures after low anterior resection for cancer.Materials and methods. A prospective randomised controlled trial enrolled 90 patients who underwent total mesorectumectomy with formation of J-pouch (J-P), side-to-end (STE) or end-to-end (ETE) anastomoses.Results and discussion. We analysed 22 J-P, 30 STE and 38 ETE patients. For technical reasons, 26.6 % J-Ps were remodelled to other anastomoses. The neorectal sensory threshold, first and permanent defecation urges and maximal tolerated volume were higher in J-P at months 3–6–12 postoperatively.Severe low anterior resection syndrome events at post-surgery month 6 were significantly more frequent in the ETE vs. J-P and STE cohorts (21, 0 and 3.3 %, respectively, p < 0.05). Stool frequency was significantly lower in J-P vs. STE and ETE at months 3–6–12. Wexner score was 3, 5, 6 at month 6 (p < 0.05) and 0, 1, 1 at month 12 for J-P, STE and ETE, respectively (p > 0.05). Evacuatory dysfunction was present at month 6 in 59.1 J-P, 33.3 STE and 21.1 % ETE.Quality of life (FIQL) in J-P and STE was significantly higher vs. ETE anastomoses in the Lifestyle (3.21, 3.22 and 3.03, respectively, p < 0.05) and Coping (3.29, 3.21 and 2.95, respectively, p < 0.05) scales to month 12 postoperatively.Conclusion. The J-pouch formation after low anterior resection ameliorates anal continence at months 3–6 post-surgery, reduces low anterior resection syndrome and improves quality of life (FIQL). The ease of implementation and irrelevance of evacuatory dysfunction in side-to-end anastomosis make it a superior choice over end-to-end surgery.